QPX7728, An Ultra-Broad-Spectrum B-Lactamase Inhibitor for Intravenous and Oral Therapy: Overview of Biochemical and Microbiological Characteristics - Lomovskaya, Olga; Tsivkovski, Ruslan; Sun, Dongxu; Reddy, Raja; Totrov, Maxim; Hecker, Scott; Griffith, David; Loutit, Jeffery; Dudley, Michael (Frontiers in Microbiology, 2021)
QPX7728 is a member of a class of cyclic boronates that gave rise to vaborbactam, the beta-lactamase inhibitor in Vabomere (meropenem-vaborbactam). In this paper we provide the overview of biochemical, structural and microbiological studies that were recently conducted with QPX7728. We show that QPX7728 is an ultra-broad-spectrum beta-lactamase inhibitor that inhibits clinically important serine beta-lactamases, including Class A and D carbapenemases from Enterobacterales and diverse Class D carbapenemases from Acinetobacter. It also inhibits many metallo beta-lactamases. It is minimally affected by general intrinsic resistance mechanisms such as efflux and porin mutations that impede entry of drugs into gram-negative bacteria. QPX7728 combinations with several IV beta-lactam antibiotics showed high potency against strains of Enterobacterales, Acinetobacter baumannii and Pseudomonas aeruginosa that are resistant to other recently approved IV beta-lactam-BLI combinations, e.g., ceftazidime-avibactam, ceftolozane-tazobactam, meropenem-vaborbactam and imipenem-relebactam. QPX7728 can be delivered orally, and its combinations with oral beta-lactams has promising activity against ESBL and carbapenemase-producing strains of Enterobacterales ensuring that ultra-broad-spectrum beta-lactamase inhibition spectrum and other features of QPX7728 could be applied to both IV and oral QPX7728-based products. Clinical development of QPX7728 has been initiated.